AUTOMATIC TEXT TRANSLATION IN THE SOCIAL MEDIA INSTAGRAM (Konferensiyalar | Conferences, 2024)
This thesis discusses the automatic text translation in the social media Instagram, the potential and challenges of automatic text translation within the Instagram ecosystem, examining its impact on user experience, content accessibility, and the fostering of global communities.